Spontaneous ureteral rupture during concurrent chemoradiotherapy in a woman with uterine cervical cancer - Shun-ichi Ikeda; Mitsuya Ishikawa; Tomoyasu Kato (Elsevier, 2015)
Spontaneous rupture of the renal pelvis and ureter is associated with obstruction of the urinary collecting system, but is rarely caused by tumors. We describe our experience with a patient who had uterine cervical cancer with mild hydroureter in whom spontaneous ureteral rupture occurred during concurrent chemoradiotherapy. The patient was a 66-year-old woman with stage IIIB uterine cervical cancer and mild hydroureter who received concurrent chemoradiotherapy. The patient felt uncontrolled right-side abdominal pain caused by ureteral rupture after she was given hydration and an intravenous bolus injection of furosemide during the first week of chemoradiotherapy. Contrast-enhanced computed tomography was more useful than ultrasonography for diagnosis of the ureteral rupture. The ureteral rupture in our patient was attributed to a rapid rise in the pressure of the urinary collecting system caused by hydration and the bolus injection of furosemide. Placement of a double-J stent before starting concurrent chemoradiotherapy may help to prevent ureteral rupture in patients who have uterine cervical cancer with mild hydroureter.